European Society For Emergency Medicine position paper on emergency medical systems' response to COVID-19. (June 2020) - Garcia-Castrillo, Luis; Petrino, Roberta; Leach, Robert; Dodt, Christoph; Behringer, Wilhelm; Khoury, Abdo; Sabbe, Marc
Abstract : The 2019 novel coronavirus acute respiratory epidemic is creating a stressed situation in all the health systems of the affected countries. Emergency medical systems and specifically the emergency departments as the front line of the health systems are suffering from overload and severe working conditions, the risk of contagion and transmission of the health professionals adds a substantial burden to their daily work. Under the perspective of European Society For Emergency Medicine, the recommendations provided by the health authorities are reviewed focus on the emergency department's activity.